2018
DOI: 10.1002/adma.201805656
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐Sensitive Broadband Photodetectors Based on Dielectric Shielded MoTe2/Graphene/SnS2 p–g–n Junctions

Abstract: Photodetectors capable of detecting light in a wide spectrum is central to diversified optoelectronic applications in spectroscopy, remote sensing, imaging and optical communication. [1] Two-dimensional (2D) transition metal dichalcogenides (TMDs) provide a tremendous potential for broadband optoelectronics due to their relatively high mobility, appropriate bandgaps, and flexibility. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In particular, TMD layers of different bandgaps and doping (p or n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 58 publications
(84 reference statements)
2
120
0
Order By: Relevance
“…Analogously, the hybrid heterostructure exhibits a broadband detection ability from ultraviolet to short‐wavelength infrared. Peculiarly, the responsivity and detectivity of the hybrid heterostructure photodetector reach up to 2.64 × 10 3 A W −1 and 1.1 × 10 13 Jones under the illumination of 1064 nm light, respectively . The performance not only exceeds the MoTe 2 /graphene and WSe 2 /graphene/MoS 2 heterostructure but also is superior to the current advanced commercial infrared photodetectors (≈10 12 Jones) requiring cryogenic cooling …”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 94%
See 3 more Smart Citations
“…Analogously, the hybrid heterostructure exhibits a broadband detection ability from ultraviolet to short‐wavelength infrared. Peculiarly, the responsivity and detectivity of the hybrid heterostructure photodetector reach up to 2.64 × 10 3 A W −1 and 1.1 × 10 13 Jones under the illumination of 1064 nm light, respectively . The performance not only exceeds the MoTe 2 /graphene and WSe 2 /graphene/MoS 2 heterostructure but also is superior to the current advanced commercial infrared photodetectors (≈10 12 Jones) requiring cryogenic cooling …”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 94%
“…Benefiting by the short transmit distance in the vertical direction, the heterostructure has shown high speed response of 24 µs and recovery of 46 µs processes . In addition, novel sandwich p‐g‐n heterostructures in which graphene acts as the middle photoactive layer and n‐type or p‐type 2DMCs as the top and down transmit layer have also shown excellent detection ability . Long et al have presented WSe 2 /graphene/MoS 2 p‐g‐n van der Waals heterostructure for broadband photodetection with a response range up to 2400 nm .…”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24] One of the most signicant investigations in 2D materials is in van der Waals heterostructure devices. 14 Multifunctional p-n diodes, 25,26 ultrasensitive photodetectors, 27,28 high-performance memories, 29,30 light-emitting diodes, 31 and bipolar junction transistors 32 have been fabricated from these materials, showing their potential application in future nanoelectronics. Although several studies on BJTs based on 2D van der Waals heterostructures can be found in the literature, [33][34][35][36][37][38] these structures have an intricate growth procedure 33,34 and tedious multistep transfer process, [35][36][37] making them difficult to fabricate.…”
Section: Introductionmentioning
confidence: 99%